2014
DOI: 10.1111/tops.12096
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Embodied and Distributional Accounts of Meaning in Language

Abstract: Over the past 15 years, there have been two increasingly popular approaches to the study of meaning in cognitive science. One, based on theories of embodied cognition, treats meaning as a simulation of perceptual and motor states. An alternative approach treats meaning as a consequence of the statistical distribution of words across spoken and written language. On the surface, these appear to be opposing scientific paradigms. In this review, we aim to show how recent cross-disciplinary developments have done m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 55 publications
3
92
0
1
Order By: Relevance
“…Extending the original ideas of Paivio (1986), some researchers have proposed that the statistical co-occurrence patterns of word-forms across discourses can give rise to a "disembodied" form of conceptual knowledge, and a number of computational studies have shown that, on the basis of such associations among word-forms, it is possible to model a variety of psycholinguistic phenomena, including priming effects, sentence completions, ambiguity resolution, and the extraction of gist from texts (Burgess & Lund, 1997;Landauer & Dumais, 1997;Griffiths et al, 2007;Jones & Mewhort, 2007). At the same time, however, there is growing agreement that, in accord with Binder and Desai's (2011) view, when tasks require detailed, meticulous conceptual processing about concrete entities and events in the world, it is usually helpful, if not necessary, to draw upon one or more of the modalityspecific systems that subserve the most relevant embodied representations Simmons et al, 2008;Dove, 2011;Louwerse, 2011;Andrews et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Extending the original ideas of Paivio (1986), some researchers have proposed that the statistical co-occurrence patterns of word-forms across discourses can give rise to a "disembodied" form of conceptual knowledge, and a number of computational studies have shown that, on the basis of such associations among word-forms, it is possible to model a variety of psycholinguistic phenomena, including priming effects, sentence completions, ambiguity resolution, and the extraction of gist from texts (Burgess & Lund, 1997;Landauer & Dumais, 1997;Griffiths et al, 2007;Jones & Mewhort, 2007). At the same time, however, there is growing agreement that, in accord with Binder and Desai's (2011) view, when tasks require detailed, meticulous conceptual processing about concrete entities and events in the world, it is usually helpful, if not necessary, to draw upon one or more of the modalityspecific systems that subserve the most relevant embodied representations Simmons et al, 2008;Dove, 2011;Louwerse, 2011;Andrews et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Embodied/distributional hybrids There have been a number of recent attempts to merge embodied and distributional approaches to semantic memory (Andrews, Frank, & Vigliocco, 2014;Andrews, Vigliocco, & Vinson, 2009;Louwerse, 2011;Lourwerse & Jeuniaux, 2008;Riordan & Jones, 2010;Vigliocco, Meteyard, Andrews, & Kousta, 2009;Vigliocco, Vinson, Lewis, & Garrett, 2004). Perhaps the greatest impetus for such accounts is the promise they have with respect to the problem of disembodiment.…”
Section: Do Multiple Problems Require Multiple Solutions?mentioning
confidence: 99%
“…According to such approaches abstract concepts are grounded in sensorimotor systems but also involve linguistic, emotional and social experiences as well as internal experiences. For example, embodied approaches could be combined with statistical/distributional approaches that emphasize the importance of linguistic experience [21]. Multiple representation views are the most promising candidates to account for abstract concepts in their diversity and variety.…”
Section: Introductionmentioning
confidence: 99%